The Translational Repressor Pumilio Regulates Presynaptic Morphology and Controls Postsynaptic Accumulation of Translation Factor eIF-4E. - Menon, K.P.; Sanyal, S.; Habara, Y.; Sanchez, R.; Wharton, R.P.; Ramaswami, M.; Zinn, K. (Neuron, 2004)
Translational repression by Drosophila Pumilio (Pum) protein controls posterior patterning during embryonic development. Here, we show that Pum is an important mediator of synaptic growth and plasticity at the neuromuscular junction (NMJ). Pum is localized to the postsynaptic side of the NMJ in third instar larvae and is also expressed in larval neurons. Neuronal Pum regulates synaptic growth. In its absence, NMJ boutons are larger and fewer in number, while Pum overexpression increases bouton number and decreases bouton size. Postsynaptic Pum negatively regulates expression of the translation factor eIF-4E at the NMJ, and Pum binds selectively to the 3'UTR of eIF-4E mRNA. The GluRIIa glutamate receptor is upregulated in pum mutants. These results, together with genetic epistasis studies, suggest that postsynaptic Pum modulates synaptic function via direct control of eIF-4E expression.